2019
DOI: 10.3390/su11030657
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Your Employees Leaving the Organization? The Interaction Effect of Role Overload, Perceived Organizational Support, and Equity Sensitivity

Abstract: Drawing on job demand-resources (JDR) theory, this study proposes that role overload and perceived organizational support have interaction effects on turnover intention. Further, we investigate the dynamics between role overload and turnover intention by considering differences in individuals' reactions to inequity. We conducted several hierarchical regression analyses to test our hypotheses using data from 207 team members at 12 manufacturing companies in South Korea. The results reveal a positive relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In crises when there are extreme shortages of resources, job demands presenting learning and autonomy opportunities can be viewed as valued sources of organizational support by employees positively impacting their intention to stay with the organization and their ability to cope with negative consequences of job demands such as BU. POS is one of the main contextual resources that is uniquely capable of explaining the impact of changes in employees' perceptions of job demands on employee outcomes (Kim et al, 2019). Fulfillment of a job demand that is presenting learning or autonomy opportunity, when there is scarcity of resources, can enhance employees' POS and, in turn, lead to positive organizational and employee outcomes (Ayoobzadeh, 2021).…”
Section: Elevated Job Demands and Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…In crises when there are extreme shortages of resources, job demands presenting learning and autonomy opportunities can be viewed as valued sources of organizational support by employees positively impacting their intention to stay with the organization and their ability to cope with negative consequences of job demands such as BU. POS is one of the main contextual resources that is uniquely capable of explaining the impact of changes in employees' perceptions of job demands on employee outcomes (Kim et al, 2019). Fulfillment of a job demand that is presenting learning or autonomy opportunity, when there is scarcity of resources, can enhance employees' POS and, in turn, lead to positive organizational and employee outcomes (Ayoobzadeh, 2021).…”
Section: Elevated Job Demands and Burnoutmentioning
confidence: 99%
“…Our choices of resources were informed by the unique setting of our study. Although POS has been extensively investigated in the JD-R-focused research as one of the main contextual resources, those investigations, however, have been limited to its moderation role (Kim et al, 2019). The current study, on the other hand, believes that the mediation role of POS is more prevalent in the unique setting of this research, where varying nature of job conditions and characteristics can change employees' perceptions of job demands and, in turn, their perception of organizational support.…”
Section: Introductionmentioning
confidence: 99%
“…According to organization support theory (Eisenberger et al, 2001), employees with high POS are better able to identify themselves with the organization (He et al, 2014) and feel obligated to help the organization achieve its goals and objectives (Hur et al, 2019). In other words, they are more willing to repay the organization's favorable treatment through continuing participation (Krishnan and Mary., 2012) instead of seeking alternative employment opportunities (Eisenberger et al, 1990). Furthermore, some research has confirmed that high POS can reduce turnover intention.…”
Section: Pos and Turnover Intentionmentioning
confidence: 99%
“…Recently, POS has been regarded as one of the organizational-related factors to predict job-crafting behavior (Cheng andO-Yang, 2018, Kim et al, 2018). Specifically, POS is viewed as the assurance that an organization not only offers employees sufficient resources (Kurtessis et al, 2015, Kim et al, 2019 but also empowers the workforce. Therefore, employees with high POS have access to adequate resources, such as an array of funding, equipment, and other forms of support (Hochwarter et al, 2006).…”
Section: The Mediating Role Of Job Craftingmentioning
confidence: 99%
“…The general level of employee engagement varies from industry to industry. Employment in the tourism and hospitality industry is characterized by a heavy workload and stress, working unsocial hours, less respect, and low rates of pay [10], which in turn lead to instability in contracts and high levels of turnover [11]. Thus, human resource management in the tourism and hospitality industry is particularly challenging and very much relevant to the study of sustainability for practitioners and academics alike.…”
Section: Introductionmentioning
confidence: 99%